The Philippine Engagement with Paulo Freire. - Cortez, Franz Giuseppe F. (KRITIKE: An Online Journal of Philosophy, 2013)
This paper is mainly a provisional survey of the engagement of the Filipinos with the thoughts of Paulo Freire, a Brazilian educator and philosopher. It presents first the main tenets of Freire's liberating pedagogy. Then, it explores the Filipinos' engagement with his ideas. Then, it gives some observations on the said engagement. Finally, it suggests a possible way on how philosophical researches in the Philippines can continually appreciate the relevance of Freire's liberating pedagogy especially in relating it to a form of Filipino philosophy that is involved in a critique of the society.